2009
DOI: 10.1111/j.1365-2044.2009.06055.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dobutamine on blood flow of free tissue transfer flaps during head and neck reconstructive surgery*

Abstract: Summary In view of the controversy over the use of inotropes in free tissue transfer surgery, we assessed the effect of different intra‐operative dobutamine infusion rates on blood flow in the anastomosed recipient artery. Twenty patients undergoing head and neck tumour resection and immediate reconstructive surgery with free tissue transfer were recruited. After completion of the microvascular anastomoses, patients received dobutamine infusions of 2, 4 and 6 μg.kg−1.min−1 in a randomised order. After steady s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 10 publications
3
26
0
Order By: Relevance
“…29,33 Dobutamine has been shown to significantly improve flap flow. 36,37 Prospective studies comparing epinephrine, norepinephrine, dobutamine, and dopexamine postoperatively demonstrated that both dobutamine and norepinephrine improved free flap skin blood flow, with norepinephrine yielding the greatest improvement. 34,35 In contrast, dopexamine and epinephrine decreased flap flow.…”
Section: Vasopressorsmentioning
confidence: 99%
“…29,33 Dobutamine has been shown to significantly improve flap flow. 36,37 Prospective studies comparing epinephrine, norepinephrine, dobutamine, and dopexamine postoperatively demonstrated that both dobutamine and norepinephrine improved free flap skin blood flow, with norepinephrine yielding the greatest improvement. 34,35 In contrast, dopexamine and epinephrine decreased flap flow.…”
Section: Vasopressorsmentioning
confidence: 99%
“…Using an ultrasonic transit time flow meter, an increase in mean and maximum blood flow with increased cardiac output was found after infusion of dobutamine in head and neck flaps (Level V Evidence). 133 Although intraoperative use of amrinone had no effect (Level V Evidence), 134 studies reported that use of phenylephrine in pig models are equivocal (Level V Evidence). 135,136 A recent prospective study examined flowthrough skin flap monitoring by laser Doppler velocimetry.…”
Section: Anesthetic Considerationsmentioning
confidence: 99%
“…As a result, many surgeons remain wary of using such agents. 4 The best agent to maintain blood pressure without adverse effect on flap blood flow remains unclear. This study investigated the effects on flap skin perfusion of four common sympathomimetic agents routinely used in intensive care practice.…”
mentioning
confidence: 99%
“…There is only one study of total blood flow to free flaps in human subjects. Scholz et al 4 investigated the effect of dobutamine on total blood flow of free tissue transfer flaps during head and neck surgery. After completion of the anastomoses, the flow in the anastomosed donor artery was measured with an ultrasonic flow meter.…”
mentioning
confidence: 99%